The politics of inequality - Pettinicchio, David (Research in political sociology ;, 2021)
In The Politics of Inequality, David Pettinicchio has gathered an interdisciplinary team of leading experts to make a valuable contribution to the existing inequalities literature through a political sociology lens. Broad social, political and economic forces associated with neoliberalism and globalization, climate change, migration and immigration, health, global financial crises, and crime and punishment, among others, have manifested themselves in a variety of different ways, in turn influencing the politics of inequality across local, national and international contexts. This volume explores a wide range of topics showcasing the multidimensional nature of the politics of inequality. Some of these topics include inequalities within democratic movements, youth political engagement, environmental justice, the impacts of neoliberal capitalism on reproductive autonomy, the politics of educational inequalities, the effects of different forms of collective action on perceptions of inequality, public health and care work, the intersection of race and LGBTQ status in political representation, and much more.